‘[Do] I Have to Get It in Writing or Something?’ What Happens When Sexuality Education Is Conceptualised Through Consent? - Giselle Woodley; Gracie Cayley; Imogen Senior; Harrison W. See; Lelia Green (Youth)
Consent education was recently introduced into the Australian curriculum, and has contributed to much of the public discourse for the past few years. However, teens’ accounts of their Relationships and Sexuality Education (RSE) classes indicate that consent is being taught to varying degrees of consistency. Qualitative data collected from 49 semi-structured interviews with 30 Australian teens (aged 11–17), with 19 interviews reprised one year later, involved teens discussing their experiences of RSE, including consent. These data were extended by 4 x teen focus groups with 18 participants. Using thematic analysis, teens’ perspectives and experiences revealed how consent appears to dominate RSE. Teens expressed dissatisfaction with how RSE was delivered and how sex is often framed in a context of safety and risk, where current framings of consent appear to contribute to fear-based messaging. Often, consent was taught as how to seek or give permission for sex or to avoid sexual assault in ways that may not reflect teens’ actual experiences. While the implementation of consent signifies welcome progress in relation to RSE, teens reveal there is still room for improvement. More positive representations of sex and sexuality are needed to balance an emphasis on safety and risk. Support is also required to help educators navigate curriculum changes, while further attention is needed to support teens’ skill development in more holistic and comprehensive aspects of sexuality and relationships.